2013
DOI: 10.5507/ag.2013.006
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in weekend number of steps in adolescents

Abstract: BACKGROUND:The activities with which young people spend the weekends do not support the prevalence of an active and healthy lifestyle enough. There are research evidence-based results that physical activity performed during weekend days is lower than physical activity in weekdays. OBJECTIVE: This study aims to find out to what extent young people achieve recommended levels of physical activity on weekends and to identify possible differences with regard to nationality or gender. METHODS: Research was realised … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 19 publications
1
5
0
4
Order By: Relevance
“…The lowest difference in daily step count between boys and girls with higher and lower PA was found on Mondays; efforts to decrease this difference even further might be especially important as a way to compensate for Sundays, as the most critical day with the lowest level of PA. The low level of PA on Sundays has been previously reported by numerous studies [20,[38][39][40][41]. The unfavourable PA on Sundays in the least physically active adolescents has not been getting any better thus far.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The lowest difference in daily step count between boys and girls with higher and lower PA was found on Mondays; efforts to decrease this difference even further might be especially important as a way to compensate for Sundays, as the most critical day with the lowest level of PA. The low level of PA on Sundays has been previously reported by numerous studies [20,[38][39][40][41]. The unfavourable PA on Sundays in the least physically active adolescents has not been getting any better thus far.…”
Section: Discussionmentioning
confidence: 74%
“…Given recent trends in adolescents' PA, one can infer that the most widespread recommendations of 10,000 steps/day [47,48], 10,000-11,700 steps/day [34], 12,000 steps/day [49,50,51], the 11,000 steps/day for both boys and girls promoted by our team [41,52,53], or 13,000-16,000 steps/day focused on weight-reduction behaviours [54], are not accepted well by adolescents with lower levels of PA. In Canada, Colley et al [50] suggested revising the recommendation from 13,500 to 12,000 steps/day among 6-19-years-old children and adolescents, which they found more appropriate benchmark for assessing the guideline of 60 min of daily moderate-to-vigorous PA.…”
Section: Discussionmentioning
confidence: 99%
“…Zatímco PA adolescentů v průběhu školních dní je v českém prostředí mapována relativně často a detailně (Mitáš et al, 2018;Rubín et al, 2018;Sigmundová, El Ansari, Sigmund, & Frömel, 2011), PA v průběhu víkendů, prázdnin a svátků je v literatuře hodnocená výjimečně (Vasickova, Fromel, Groffik, & Chmelik, 2013), a to i přesto, že toto období tvoří téměř polovinu celého roku (Česká republika 46,3 %, Slovensko 48,5 %, Rakousko 50,7 % a Francie 55,6 % neškolních dnů v roce) (Eurostat, 2018). Dle Brooke et al (2014) jsou žáci aktivní (MVPA) 82,3 ± 44,0 minut během průměrného školního dne a 68,3 ± 43,9 minut ve dnech víkendových a pokles PA žáků o víkendu potvrzují taktéž tuzemské studie (Frömel, Kudlacek, Groffik, Chmelik, & Jakubec, 2016;Vasickova, Fromel, Groffik, & Chmelik, 2013). I na základě využití moderních technologií monitoringu a lokalizace PA (GPS + geoinformační systémy + akcelerometrie) je doporučováno směrovat intervence s cílem zvýšení PA právě do dnů mimo školní docházku (Bürgi & de Bruin, 2016).…”
Section: úVodunclassified
“…Zdravotní doporučení pro PA (alespoň 60 minut MVPA/ den) plní v sobotu dle našeho šetření téměř 60 % českých adolescentů. Předchozí studie zkoumající PA adolescentů v České republice však došla k závěru, že zdravotní doporučení pro PA plní v rámci víkendových dní pouze 43 % chlapců a 44 % dívek (Vasickova et al, 2013). Domníváme se, že hlavním faktorem, který má vliv na existenci rozdílu těchto výsledků je metodika studie.…”
Section: Diskuzeunclassified
See 1 more Smart Citation